Experimental study on direct-contact liquid film cooling simulated dense-array solar cells in high concentrating photovoltaic system. (1st March 2017) - Wang, Yiping; Shi, Xusheng; Huang, Qunwu; Cui, Yong; Kang, Xue
Highlights: Direct-contact liquid film cooling dense-array solar cells was first proposed. Average temperature was controlled well below 80 °C. The maximum temperature difference was less than 10 °C. The heat transfer coefficient reached up to 11.91 kW/(m 2 ·K) under 589X. Abstract: This paper presented a new method of cooling dense-array solar cells in high concentrating photovoltaic system by direct-contact liquid film, and water was used as working fluid. An electric heating plate was designed to simulate the dense-array solar cells in high concentrating photovoltaic system. The input power of electric heating plate simulated the concentration ratios. By heat transfer experiments, the effect of water temperatures and flow rates on heat transfer performance was investigated. The results indicated that: the average temperature of simulated solar cells was controlled well below 80 °C under water temperature of 30 °C and flow rate of 300 L/h when concentration ratio ranged between 300X and 600X. The maximum temperature difference among temperature measurement points was less than 10 °C, which showed the temperature distribution was well uniform. The heat transfer coefficient reached up to 11.91 kW/(m 2 ·K) under concentration ratio of 589X. To improve heat transfer performance and obtain low average temperature of dense-array solar cells, lower water temperature and suitable water flow rate are preferred.